Nucleolin mediates nucleosome disruption critical for DNA double-strand break repair - Goldstein, Michael (National Academy of Sciences, 2013)
Recruitment of DNA repair factors and modulation of chromatin structure at sites of DNA double-strand breaks (DSBs) is a complex and highly orchestrated process. We developed a system that can induce DSBs rapidly at defined endogenous sites in mammalian genomes and enables direct assessment of repair and monitoring of protein recruitment, egress, and modification at DSBs. The tight regulation of the system also permits assessments of relative kinetics and dependencies of events associated with cellular responses to DNA breakage. Distinct advantages of this system over focus formation/disappearance assays for assessing DSB repair are demonstrated. Using ChIP, we found that nucleosomes are partially disassembled around DSBs during nonhomologous end-joining repair in G1-arrested mammalian cells, characterized by a transient loss of the H2A/H2B histone dimer. Nucleolin, a protein with histone chaperone activity, interacts with RAD50 via its arginine-glycine rich domain and is recruited to DSBs rapidly in an MRE11-NBS1-RAD50 complex-dependent manner. Down-regulation of nucleolin abrogates the nucleosome disruption, the recruitment of repair factors, and the repair of the DSB, demonstrating the functional importance of nucleosome disruption in DSB repair and identifying a chromatin-remodeling protein required for the process. Interestingly, the nucleosome disruption that occurs during DSB repair in cycling cells differs in that both H2A/H2B and H3/H4 histone dimers are removed. This complete nucleosome disruption is also dependent on nucleolin and is required for recruitment of replication protein A to DSBs, a marker of DSB processing that is a requisite for homologous recombination repair.